2009
DOI: 10.1093/jxb/erp223
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism for jasmonate-induction of anthocyanin accumulation in Arabidopsis

Abstract: Anthocyanins are important plant pigments that fulfil many physiological and ecological functions. Anthocyanin biosynthesis is controlled by numerous regulatory factors at the transcriptional level. Jasmonates (JAs) has been shown to induce anthocyanin accumulation in several plant species, however, the molecular mechanism for JA-regulated anthocyanin accumulation remains unknown. In this study, genetic, molecular, and physiological approaches were used to reveal the molecular basis of JA-regulated pigmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
269
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(287 citation statements)
references
References 58 publications
16
269
0
2
Order By: Relevance
“…Trichome formation, which is not affected in myc2 mutants (Yoshida et al, 2009), was reduced in ProJAM1:JAM1-SRDX plants (see Supplemental Figure 4 online). These phenotypes are probably due to the impaired JA responsiveness of JAM1 CRES-T plants because JA mediates anthocyanin biosynthesis and trichome formation (Shan et al, 2009;Yoshida et al, 2009;Qi et al, 2011).…”
Section: Jam1 Affects Ja Responses and Growthmentioning
confidence: 99%
“…Trichome formation, which is not affected in myc2 mutants (Yoshida et al, 2009), was reduced in ProJAM1:JAM1-SRDX plants (see Supplemental Figure 4 online). These phenotypes are probably due to the impaired JA responsiveness of JAM1 CRES-T plants because JA mediates anthocyanin biosynthesis and trichome formation (Shan et al, 2009;Yoshida et al, 2009;Qi et al, 2011).…”
Section: Jam1 Affects Ja Responses and Growthmentioning
confidence: 99%
“…Because JA mutants have not been available, it is not surprising that JA has not been implicated in the regulation of anthocyanin biosynthesis in monocots. However, a number of studies have shown that JA induces anthocyanin accumulation in several dicotyledonous plants (Shan et al, 2009). JA-regulated pigmentation in Arabidopsis was shown to be dependent on JA signaling SCF-COI1 complex interacting with WD-repeat/bHLH/MYB complexes (Qi et al, 2011).…”
Section: Anthocyanin Pigmentation In Brace Roots Requires Jamentioning
confidence: 99%
“…A recent finding that the photosynthetic electron transport (PET) chain, in addition to the well-characterized HY5-dependent signaling, plays an important role in light signaling pathways in green, vegetative leaf tissues (Das et al, 2011;Jeong et al, 2010) demonstrates the complexity of the cross-talk between various pathways. Sugar-induced anthocyanin biosynthesis is apparently modulated by the heterotrimeric M(L2)BW complexes that are under the regulation of hormones (Das et al, 2012;Jeong et al, 2010;Loreti et al, 2008;Shan et al, 2009), Fig. 1.…”
Section: Introductionmentioning
confidence: 99%